AN IOT-ENABLED SYSTEM FOR SUSTAINABLE BOREHOLE WATER MANAGEMENT - Kwaghtyo, Dekera Kenneth; Obilikwu, Patrick; Iorzua, Joseph Tersoo; Orgem, Emmanuel; Gaav, Terseer Andrew; Odey, Omeka Friday (FUDMA Journal of Sciences, 2025)
Groundwater resources in the Lafia metropolis face increased pressure due to unsustainable borehole usage practices. This study leverages the Internet of Things (IoT) to design a device for the sustainable management of groundwater extraction through borehole systems. The system was developed by integrating an ESP8266 Wi-Fi microcontroller, a mechanical pump timer, and the Arduino IoT Cloud for remote control and real-time monitoring. Over a three-day test period, the system achieved a high uptime efficiency of 97.8%, demonstrating improved automation and operational reliability. Compared with existing methods, the proposed system offers enhanced scheduling, lower maintenance requirements, and minimal human intervention. This work contributes to sustainable water management efforts, particularly in low-resource settings, by leveraging affordable and accessible IoT technology.
Keywords: Groundwater Extraction; Sustainable Aquifer Management; IoT Device; Borehole Regulation; Real-Time Monitoring